2022
DOI: 10.2147/jep.s362258
|View full text |Cite
|
Sign up to set email alerts
|

Meriandra dianthera Aqueous Extract and Its Fraction Prevents Blood Coagulation by Specifically Inhibiting the Intrinsic Coagulation Pathway: An in vitro Study

Abstract: Background: Currently, cardiovascular disorders are the primary cause of mortality in the world and constitute a serious medical problem. Blood coagulation is an essential process to prevent excessive blood loss through injured blood vessels; however, abnormal blood clotting in the blood vessels can result in fatal cardiovascular disorders. This study investigated the in vitro anticoagulant activity of Meriandra dianthera crude extract and its fractions and their erythrocyte membrane stabilizing activity. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…17 Previous studies also reported anticoagulant and antiplatelet effects of different plant extracts. 14,17,18,23,24,25,26 Similar to the present results, the EtOAc fractions of Canna species were proved to exhibit the most potent antiaggregatory and anticoagulant activity among fractions. 17,18 Further investigation led to the identification of antithrombotic compounds from the EtOAc fraction of Canna plants.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…17 Previous studies also reported anticoagulant and antiplatelet effects of different plant extracts. 14,17,18,23,24,25,26 Similar to the present results, the EtOAc fractions of Canna species were proved to exhibit the most potent antiaggregatory and anticoagulant activity among fractions. 17,18 Further investigation led to the identification of antithrombotic compounds from the EtOAc fraction of Canna plants.…”
Section: Discussionsupporting
confidence: 83%
“…14,17,24 The extracts from leaves of Meriandra dianthera also expressed anticoagulant effects on APTT and PT. 23 The potential antiplatelet and anticoagulant activity of the aerial PO suggests that PO is a promissory candidate for the development of alternative therapies or supplementary products to prevent and treat CVDs. The detected antithrombotic effect of the PO aerial part could be explained by the abundant phytochemicals present in the plant, including flavonoids, terpenoids, carotenoids, alkaloids, polysaccharides, sterols, fatty acids, proteins, vitamins, and minerals.…”
Section: Discussionmentioning
confidence: 99%
“…APTT is an essential metric for assessing the internal coagulation pathway. 44 An increased APTT signifies abnormalities in coagulation factors and disruptions in internal coagulation. In our study, Cox multifactorial analysis revealed that an increased APTT is an independent risk factor for 28-day mortality in patients with SA-AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Time of coagulation was calculated [23]. The PT assay gives a clear picture of the extrinsic pathway factors [39].…”
Section: In Vitro Blood Coagulation Studymentioning
confidence: 99%